RESISTANCE TO ANTIPLATELET DRUGS (ASPIRIN, CLOPIDOGREL) IN PATIENTS UNDERGOING ELECTIVE PERCUTANEOUS CORONARY INTERVENTION - V. A. Sulimov; E. V. Moroz (Столичная издательская компания, 2015)
Aim. To study prevalence of resistance to acetylsalicylic acid, clopidogrel and dual resistance in percutaneous coronary intervention (PCI), to identify clinical risk factors of resistance development, to study effects of concomitant therapy on resistance development, to identify relationship between risk of cardiovascular complications and activity of platelet aggregation, to assess safety of dual antiplatelet therapy , and to suggest possible ways to overcome clopidogrel resistance. Material and Methods. Patients (n=100) with stable angina class II-IV, that were planned for PCI, were included in the study. Patients randomized to group A (n=53) received clopidogrel 75 mg daily for 7 days before PCI, and later were allocated to subgroups of clopidogrel sensitive or resistant depending on platelet aggregation. In resistant subgroup clopidogrel daily dose was increased to 150 mg for the whole next period of observation. Patients randomized to group B (n=47) received a loading dose of clopidogrel 300 mg one day before PCI. Depending on the results of platelet reactivity assessment, patients were split into sensitive or resistant subgroups. Patients of resistant subgroup received the second loading dose of clopidogrel 300 mg before PCI and started to take clopidogrel 150 mg daily after PCI. Patients of sensitive subgroup did not receive the second clopidogrel loading dose and started to take clopidogrel in usual daily dose of 75 mg. The combined endpoint (after 6 and 12 months) included cardiovascular death, recurrent nonfatal myocardial infarction, recurrent angina, acute ischemic stroke, acute impairment of peripheral circulation. Results. Increased reactivity of platelets to acetylsalicylic acid was detected in 21% of patients. Resistance to clopidogrel in both groups was 56%. Double resistance was registered in 8% of patients. The development of resistance to clopidogrel was related with obesity (p=0.014) and hyperglycemia (p=0.017). 4 and 11 cardiovascular events were registered in 6 and 12 months, respectively. Conclusion. To assess efficacy of antiplatelet therapy it is advisable to study platelet aggregation before and shortly after PCI, especially in patients with obesity and glucose metabolism disturbances. Knowledge of changes in platelet aggregation during clopidogrel therapy can be usefull for timely correction of antiplatelet therapy. Increase in clopidogrel dose up to 150 mg a day is one of the possible way to overcome resistance to clopidogrel.